Дослідження методів збільшення динамічного діапазону цифрових звукозаписів - Магаляс, В. С. (ХНУРЕ, 2019)
In this paper we analyzed the ability of increase the dynamic range of digital audio. Some methods of reduce the quantization noise audibility in digital audio signals is consider. The method of dithering is analyzed. Dithering parameters is investigate, such as the amplitude, spectrum and the probability distribution function of the noise amplitude. It is show that all dithering parameters give a good decorrelation of the quantization noise. Dithering noise with a triangular probability distribution reduces the audibility of quantization noise, despite the significant decrease of the signal-to-noise ratio.